Analisis pendapatan pengrajin usaha industri rumah tangga pengolahan kerupuk udang di Kecamatan Tungkal Ilir Kabupaten Tanjung Jabung Barat - Septiati, Anisa; Zulfanetti, Zulfanetti; Achmad, Erni (e-Journal Perdagangan Industri dan Moneter, 2018)
The main subjective of this research are to analyze the socio-economic characteristics of home industry and analyze the effect of income. The data used in this study are primary data obtained by field research which was sourced from home industry businessman processing shrimp crackers as a sample. The sampling method used in this study is Stratified Ramdom Sampling. The analysis tool uses multiple linear regression.The study found that the characteristics of the home industry businessman processing shrimp of respondents based on age over 41 years as such as 43,59 percent, senior high school level 48,72 percent, the number of family members 3-4 people 34,62 percent, business duration 1-10 years 39,74 percent and the income of the industry businessman processing shrimp crackers above Rp 4.100.000,- amounting to 55,13 percent. Based on the results of data processing, it is obtained that the capital variables coefficient is -1.606645 and the raw material coefficient is 92521.55 which has a significant effect on the home industry businessman processing shrimp crackers processing. While the labor variable coefficient of 288028.4 which had no significant effect on the income of home industry businessman processing shrimp crackers. Keywords: Income, Characteristics of home industry businessman, Multiple linier regression analysis.